Implementasi Pedoman Mengadili Kasus Dispensasi Perkawinan Oleh Hakim Pengadilan Agama Jepara Berdasarkan Prinsip Kepentingan Terbaik Anak - Rosyada, Amrina (Isti`dal : Jurnal Studi Hukum Islam, 2025)
Marriage dispensation in Jepara has increased significantly in the last two years, starting from 2020-2021. This increase indicates about the high possibility of children marriage in Jepara. According to the cases and the data, it is still necessary to analysing the basic of the consideration about the court judgement which allowed the application of children marriage dispensation in Jepara based on the guidebook of the marriage dispensation (Perma Number 5 of 2019) to ensure the best concerns of the children in Jepara. The method of this research used qualitative methods with a non-doctrinal field approach and an empirical/sociological-inductive logical approach. The result of this study show’s that the judges at the Jepara Religious Court preserve the children concerns properly to determine their judgement and carry out Perma Number 5 of 2019 truly, based on the Guidelines to adjudicate the Applications for Marriage Dispensation.